(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article outlines existing problems in improving the innovative well-being of the higher education system of the Republic of Uzbekistan, the acceptance of students in societies, the scientific well-being of teachers, and the existing material and technological base for the implementation of scientific research in higher education institutions.